Noninvasive quantitative imaging of selective microstructure sizes via magnetic resonance - Capiglioni, Milena Sofía (2021)
Extracting quantitative microstructure information of living tissue by noninvasive imaging is an outstanding challenge for understanding disease mechanisms and allowing early stage diagnosis of pathologies. Magnetic resonance imaging (MRI) is a promising and widely used technique to pursue this goal, but still provides low resolution to reveal microstructure details. We here report on a method to produce images of filtered microstructure sizes based on selectively probing the nuclear-spin dephasing induced by the molecular diffusion within specific tissue compartments. The microstructure-size filter relies on suitable dynamical control of nuclear spins that sense magnetization "decay shifts"rather than the commonly used spin-echo decay rates. The feasibility and performance of the method are illustrated with proof-of-principle experiments and simulations on typical size distributions of white matter in the mouse brain. These results position spin-echo decay shifts as a promising MRI tool as they could offer the ability to perform noninvasive histology without assuming a microstructure distribution model. This sets a step towards unraveling diagnostic information based on microscopic parameters of biological tissue.